Assessment of Various Tooth Brushing Techniques and its Association with Dental Plaque: Tooth Brushing Techniques and its Association with Dental Plaque - Saba Shah, Syeda Lalarukh; Hameed, Aamir; Sana, Ruqayya; Khalil, Zia ur Rehman (Pakistan Journal of Health Sciences, 2024)
Dental plaque and poor oral hygiene are well-known risk factors for gingivitis, periodontitis, and other dental diseases. Using a manual toothbrush to remove plaque mechanically is essential for maintaining good oral hygiene every day and avoiding dental problems. Consequently, different toothbrushes are assessed to evaluate their effectiveness in plaque removal. Objective: To find the association between types of tooth brushing techniques and dental plaque in school children. Methods: A cross-sectional study was conducted in schoolchildren aged 15-18 years and convenience sampling was used to get data from the sample size of 211. Utilizing SPSS version 26.0, the data were examined to determine frequencies and percentages. The chi-square test was utilized to investigate potential associations of plaque with brushing techniques. Results: It showed that 58.3% of the children were male, while 41.7% were female. A majority (76.8%) used toothpaste, 59.2% brushed once daily, a smaller group brushed thrice a day (10%) and 45% have never visited a dentist. The Modified Bass technique proved the most effective, with 42.2% showing no plaque. The vertical and combined techniques showed moderate plaque levels, highlighting the significant impact of the brushing technique on plaque accumulation, as shown by the p-value of <0.001. Conclusion: The study revealed that the Modified Bass technique had the highest rate of reducing plaque, while horizontal brushing showed the greatest plaque buildup.